Hungary : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
This Selected Issues paper for Hungary highlights the monetary policy framework in Hungary and the models used by the central bank (MNB). The MNB's Quarterly Projection Model combines neo-Keynesian features in the short term with neoclassical features in the long term. It is a two-sector small-open-economy model, estimated by Bayesian methods. Fiscal policy is modeled using various revenue and expenditure items. Rich in sectoral details and structural shocks, the model generates impulse responses of different variables to structural shocks.